Mfengu beach labour and Port Elizabeth harbour development - E.J. Inggs (Contree, 2024)
The loading and unloading of ships at Port Elizabeth remained virtually unchanged between 1820 and 1870. Everything was loaded into surfboats which had to negotiate Algoa Bay's notorious breakers. The surfboats were propelled between the roadstead and the shore by means of a system of warps or ropes. The cargoes were manhandled into or out of the beached boats by labourers who, depending on the tide, had to wade through the shallows. This labour was monopolised by members of the Mfengu tribe from after the Sixth Frontier War (1834 - 1835) up until the cattle killing episode of 1857. Because no other method was used until the construction of a system of jetties between 1869 and 1902, the Mfengu beach labourers had considerable powers for negotiating better wage rates. They were subsequently responsible for South Africa's first recorded strike on 9 November 1846 when they struck for higher wages.